Problem Solving Skill in Physics Learning: Systematic Literature Review - Muhammad Hilmi Nasir; Restu Widiatmono; Heru Kuswanto (Jurnal Penelitian Pendidikan IPA, 2025)
A systematic literature review on problem solving skills in physics learning has been done. The purpose of this literature review is to discuss aspects that affect problem solving skills in physics and determine the proper learning method to improve problem solving skills in physics. The method used in writing this article is literature review. Literature was searched by accessing electronic databases online from Scopus. At the beginning of the search in the Scopus database using the keywords problem solving, physical education, students. 35 articles were obtained that were in accordance with the research topic, and limited publications for the last 5 years. Through this literature review, it was found that problem solving ability in physics learning is influenced by the relationship with the students themselves, teachers, and the school environment. The selection of effective learning models and media can improve problem solving skills in physics learning, such as the use of STEM-based Project Based Learning (PjBL) models, inquiry learning models, causal reasoning learning models, and the application of CPSPL (cooperative problem solving physics) models, as well as the use of module, web-based learning and interactive multimedia can improve student's problem solving skills.